2023
DOI: 10.3390/molecules28041517
|View full text |Cite
|
Sign up to set email alerts
|

Determining RNA Natural Modifications and Nucleoside Analog-Labeled Sites by a Chemical/Enzyme-Induced Base Mutation Principle

Abstract: The natural chemical modifications of messenger RNA (mRNA) in living organisms have shown essential roles in both physiology and pathology. The mapping of mRNA modifications is critical for interpreting their biological functions. In another dimension, the synthesized nucleoside analogs can enable chemical labeling of cellular mRNA through a metabolic pathway, which facilitates the study of RNA dynamics in a pulse-chase manner. In this regard, the sequencing tools for mapping both natural modifications and nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“… 34 They occur in all major classes of RNA, including mRNA, transfer RNA (tRNA), ribosomal RNA (rRNA), and non-coding RNA (ncRNA), and are generally conserved across species. 35 The presence of m 4 C in RNA was originally discovered in bacterial rRNA, where it was found to play a significant role in ribosome function and protein synthesis. 36 Recent studies have revealed the presence of m 4 C modifications in eukaryotic RNA and have identified methyltransferase like 15 (METTL15) as the enzyme responsible for the m 4 C installation.…”
Section: Resultsmentioning
confidence: 99%
“… 34 They occur in all major classes of RNA, including mRNA, transfer RNA (tRNA), ribosomal RNA (rRNA), and non-coding RNA (ncRNA), and are generally conserved across species. 35 The presence of m 4 C in RNA was originally discovered in bacterial rRNA, where it was found to play a significant role in ribosome function and protein synthesis. 36 Recent studies have revealed the presence of m 4 C modifications in eukaryotic RNA and have identified methyltransferase like 15 (METTL15) as the enzyme responsible for the m 4 C installation.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of Se -allyl- l -selenohomocysteine ( Se AHC) and methionine adenosyl transferase (MAT), allyl- Se AM was in situ generated, and the m 6 A methylase METTL3-METTL14 heterodimer transferred the allyl group from allyl- Se AM to the N 6 -position of specific adenosine in the consensus sequence of the RNA substrate. The a 6 A site on RNA can be detected by a chemical sequencing method. The a 6 A-modified A-Pepper was first enriched through antibody immunoprecipitation and was then subjected to iodination by transforming a 6 A to 1, N 6 -cyclized adenosine (cyc-A). The chemically treated RNA was reversely transcribed into cDNA, and cDNA was amplified and sequenced for the detection of base misincorporation at the opposite site of cyc-A during reverse transcription (RT).…”
Section: Results and Discussionmentioning
confidence: 99%
“…These approaches prove highly valuable for investigating the lifetime and dynamics of nascent transcripts. While 4SU is suboptimal for examining the turnover of uridine‐tailed RNAs, pseudouridylated RNAs, and uridine‐poor RNAs [68] . The creation of novel nucleoside analogs with chemical sequencing capabilities should not only address these limitations but also enable dual‐labeling applications.…”
Section: Discussionmentioning
confidence: 99%